2008
DOI: 10.1094/cm-2008-0730-01-rv
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-Efficiency Fertilizers for Use on the Canadian Prairies

Abstract: In spite of the management practices adopted by Canadian producers to mimize fertilizer losses, N‐use efficiency is normally estimated to be less than 50% in the year of application. Various types of enhanced‐efficiency fertilizers such as nitrification inhibitors, urease inhibitors, and coated N fertilizers are available that attempt to address the constraints associated with traditional N management in order to improve N‐use efficiency and/or the operational efficiency of Canadian agricultural systems. Enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The EEFs extend the duration of release/availability of N nutrition to the plant and thereby better match the time of N nutrient availability with crop demand. Subsequently, EEFs may increase fertilizer N recovery efficiency, reduce potential N losses to the environment and improve yield (Grant and Wu 2008;Motavalli et al 2008).…”
Section: Enhanced Efficiency Fertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEFs extend the duration of release/availability of N nutrition to the plant and thereby better match the time of N nutrient availability with crop demand. Subsequently, EEFs may increase fertilizer N recovery efficiency, reduce potential N losses to the environment and improve yield (Grant and Wu 2008;Motavalli et al 2008).…”
Section: Enhanced Efficiency Fertilizersmentioning
confidence: 99%
“…The challenge with adoption of EEFs in cereal crops is their relatively high cost, typically 10 to 40% higher as compared with conventional fertilizers (Olson-Rutz et al 2009). Particularly under conditions where there is low potential for N loss, the use of EEFs may not offer significant benefit to offset the increased cost (Grant and Wu 2008;Motavalli et al 2008). However, manufacturing costs are decreasing and lower-priced controlled-release fertilizers such as ESN (i.e., environmentally smart nitrogen, Agrium, Calgary, AB) has been released to the market, which may make use of EEFs more economical for cereal crop production systems (Grant and Wu 2008).…”
Section: Enhanced Efficiency Fertilizersmentioning
confidence: 99%
“…Banding N fertilizers at planting as side-banding (placing the fertilizer in a narrow band 2.5 to 8.0 cm to the side and/or 2.5 to 8.0 cm below the seed) or midrow-banding (placing the fertilizer between every second seed row 2.5 to 8.0 cm below the seed) is usually recommended for annual crops. Banding N fertilizer provides greater fertilizer N use effi ciency than broadcast-incorporation (Grant and Wu, 2008;Lemke et al, 2009;Malhi et al, 1996;Racz, 1979).…”
mentioning
confidence: 99%
“…Controlled release fertilizer is one approach to increasing fertilizer efficiency by synchronizing nutrient release with crop demand and thereby minimizing environmental losses (Blaylock et al, 2005; Shoji et al, 2001; Morgan et al, 2009). Polymer‐coated urea is one type of controlled release fertilizer (Grant and Wu, 2008; Nelson et al, 2008). A limited number of studies comparing polymer‐coated urea with urea have indicated that crop yield can be lower, unchanged, or higher depending on the crop and growing conditions (McKenzie et al, 2007; Nelson et al, 2008; Noellsch et al, 2009).…”
mentioning
confidence: 99%